Filicides - a case series analysis. Issue 2 (4th March 2023) - Hellen, Florence; Verhülsdonk, Sandra; Janssen, Birgit; Ritz-Timme, Stefanie; Hartung, Benno
ABSTRACT: Filicides lead to questions about motives and missed opportunities for prevention. The development of preventive strategies is difficult due to heterogeneous perpetrator-victim dynamics. Eighteen child killings by parents over a period of 10 consecutive years in the catchment area of Dusseldorf's Institute of Legal Medicine were identified, and the autopsy reports and prosecution files were analysed. With regard to motives and psychodynamics, a heterogeneous group of perpetrators were identified; the perpetrators were responsible for 8 accidental filicides, 3 killings of unwanted children, 1 killing during perpetrator psychosis, 1 spousal revenge killing and 5 homicide-suicides. Except for the homicide-suicides, overburdening seemed to be the main risk factor for the killings. Preventive measures are difficult to establish. They should focus on awareness campaigns and increasing or establishing multi-professional support for affected families.